2009
DOI: 10.1007/s10834-009-9173-8
|View full text |Cite
|
Sign up to set email alerts
|

Employed Rural, Low-Income, Single Mothers’ Family and Work Over Time

Abstract: Demands, Low-income, Resource, Single mothers, Work-family conflict,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…In a review of literature about struggling to care for their children, a number of studies were found that specifically discussed the experience of stress suffered by single mothers in caring for their child/children (Holland , Son & Bauer ). The findings of these studies were similar to those of this study in which work–life balance was a point of significant stress for the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of literature about struggling to care for their children, a number of studies were found that specifically discussed the experience of stress suffered by single mothers in caring for their child/children (Holland , Son & Bauer ). The findings of these studies were similar to those of this study in which work–life balance was a point of significant stress for the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Competing demands from family and work were cited by Son & Bauer () as contributing factors to the quality of care provided by single mothers in their study of 28 rural, low‐income single mothers across 11 states of the United States of America. The study, which adopted a human ecology perspective to understand how low‐income single mothers managed their family and work lives, found that demands from the workplace, including non‐stable work hours and job insecurity, contributed significantly to family stress impacting on the ability of the mother to provide what the participants' considered to be appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of family characteristics, having more than one child (Steiber, 2009), older children (Baxter & Alexander, 2008), lower level of education, and a poorer financial situation (Ciabattari, 2007) are associated with higher WFC. Finally, problems with childcare arrangements are likely to be positively associated with WFC (Baxter & Alexander, 2008;Son & Bauer, 2010).…”
Section: The Present Studymentioning
confidence: 99%
“…And this article has been done to find out the relationship between management activity of married women within family businesses and perceived well-being controlling for work roles, family context, personal and financial resources. The next by Distelberg and Blow (2010) discussed the literature about work-family balance field which has explored the validity of an ecosystems perspective (Seery, Corrigall, & Harpel, 2008;Son & Bauer, 2010;Voydanoff, 2002) and found validity in viewing this family-work balance issues through the lens of ecosystems. The final by Brewton, Danes, Stafford, and Haynes (2010) agreed with that the negative relationship between crossover of family and business tasks and resilience for rural firms.…”
Section: Stated In Literature Review But Not Analysedmentioning
confidence: 99%